Pemikiran Kuntowijoyo Tentang Profetik dan Pelaksanaannya pada Kurikulum Pendidikan Agama Islam - Rismayanti Harahap; Ismail; Herry Syahbannuddin Nst (Jurnal Penelitian dan Ilmu-Ilmu Keislaman, 2023)
The type of this research is this research is a type of library research (library research), namely research whose object of study uses library data in the form of books as a data source. The results of the study note that Kuntowijoyo's prophetic values ​​consist of three pillars, namely: humanization, liberation and transcendence which are derived from the Qur'an in Ali Imran verse 110. The concept of humanization is to humanize humans, eliminate material things, dependency, violence and hatred from humans. The liberation that Kuntowijoyo means in prophetic social science is in the context of science and not in an ideological context; namely knowledge based on transcendental noble values. In such a way, these liberative values ​​must be understood or positioned in social science which has a prophetic responsibility to liberate human beings from the cruelty of poverty, the exploitation of abundance, the domination of oppressive structures and the hegemony of false consciousness. Meanwhile, transcendence is the most important element of prophetic ethics which also forms the basis of the other two elements; humanization and liberation. Transcendence gives direction to where and for what purpose humanization and liberation are carried out. The implications of pfofetic values ​​for the development of the PAI curriculum are: In developing the PAI curriculum in the future, in addition to maintaining its characteristics which prioritize efforts to internalize the values ​​of Islamic teachings, whether in the form of 'aqidah, shari'ah or morality, it can also increase the portion of aspects of social change as the demands of the times. This effort is intended to increase the portion of efforts to instill human and social values. The content of Divine values ​​and human values ​​must have a balanced portion. In developing the PAI curriculum in schools, apart from being able to create students who have strong faith and piety in dealing with global developments and world trends, they also have a high sense of social concern for injustice in their society and are able to participate actively in developing society towards the desired progress.